Proposal for nationwide registration of injuries or fatalities in wheelchair user motor vehicle passengers in Japan - Masahito Hitosugi; Ayumu Kuwahara; Mami Nakamura (Komiyama Printing Co. Ltd, 2024)
One consequence of population aging is an increase in the number of older wheelchair users. They often board the motor vehicle from the rear for moving. Recently, wheelchair user vehicle passengers have involved in motor vehicle collisions and died. A three-point seatbelt does not adequately fit most wheelchair user passengers because of the way that the wheelchair is constructed. Therefore, owing to the movement of the body immediately after the collision, the wheelchair user passengers attacked their body to the interior of the vehicle or suffered from the intrusion of the lap belt into the abdomen, subsequently suffered from severe head, chest or abdominal injuries. According to the review of all fatal motor vehicle collisions in Shiga Prefecture, Japan, which has a population of approximately 1.4 million, from 2017 to 2022, the rate of wheelchair users in fatal motor vehicle passenger increased from 3.6% in 2017 to 2019 to 7.8% in 2020 to 2022. Therefore, there is a risk that substantial numbers of wheelchair user passengers involved in motor vehicle collisions will die. However, in Japan, there are no official statistics on the involvement of wheelchair user passengers in motor vehicle collisions. Therefore, we propose a nationwide registration of injuries and fatalities in wheelchair user passengers. Investigating the mechanisms of injury in wheelchair user passengers would contribute to the development of safety measures, especially for restraint systems. Established preventive measure would contribute to the decrease of fatally or severely injured motor vehicle collision passengers.